Identification of Polyphenols from Chilean Brown Seaweeds Extracts by Lc-Dad-Esi-Ms/Ms - Gimenez-Castillo, B (Taylor and Francis Inc., 2019)
Polyphenol profiles were characterized in extracts of three Chilean brown seaweeds, Durvillaea antarctica (Chamisso) Hariot, Lessonia spicata (Suhr) Santelices, and Macrocystis integrifolia (Bory) by liquid chromatography with mass spectrometry detection (LC-MS/MS). Phlorotannins with different degrees of polymerization were identified in D. antarctica (trimers to octamers) and L. spicata (trimers to tetramers). No signals related to phlorotannins compounds were detected in M. integrifolia. L. spicata and M. integrifolia showed a great variety of flavonoid compounds in comparison with D. antarctica, mainly identified as glycoside forms in all the extracts. The antioxidant activity of brown seaweed extracts measured by ferric reducing power (FRAP) and oxygen radical absorbance capacity (ORAC) was significantly higher in D. antarctica, followed by M. integrifolia and L. spicata, in line with the total phenolic (TP) content. However, D. antarctica and M. integrifolia showed similar activity for free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) in spite of the differences found in TP content. D. antarctica as well as L. spicata would represent a potential source of phlorotannins, whereas M. integrifolia could be considered as an alternative source of flavonoids. The identification of polyphenols in extracts of Chilean brown seaweeds opens innovative opportunities for their use in the food and pharmaceutical industries. © 2019, © 2019 Taylor & Francis Group, LLC.